2014
DOI: 10.1371/journal.pone.0108574
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Executive Dysfunction after Acute Infarct

Abstract: AimThe aim of this study was to investigate the association of infarct location with post-stroke executive dysfunction.MethodsOne hundred seventy-seven patients hospitalized with acute infarction were enrolled. General information and NIHSS score at admission were recorded. The infarct site was recorded from magnetic resonance T2-W1 and FLAIR images, and the extent of white matter disease was assessed using the Fazekas score. Seven days after symptoms, executive function was assessed using the validated Chines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…Further analyses of patients with this ischemic stroke pattern may elucidate underlying pathophysiology or imaging correlates explaining this heterogeneity [e.g., grade of capsule ischemia and preexisting white matter lesions ( 20 )]. Furthermore, patients with iSCI were found to frequently suffer from different degrees of less conspicuous neuropsychological dysfunctions ( 4 , 46 ). This may be of relevance as more than half of the acute stroke patients who achieve an excellent functional outcome suffer from cognitive impairment, depression, or participation restriction within 3 years after the acute event ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Further analyses of patients with this ischemic stroke pattern may elucidate underlying pathophysiology or imaging correlates explaining this heterogeneity [e.g., grade of capsule ischemia and preexisting white matter lesions ( 20 )]. Furthermore, patients with iSCI were found to frequently suffer from different degrees of less conspicuous neuropsychological dysfunctions ( 4 , 46 ). This may be of relevance as more than half of the acute stroke patients who achieve an excellent functional outcome suffer from cognitive impairment, depression, or participation restriction within 3 years after the acute event ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…We found that the executive function impairment was associated with disruption of WM tracts in the frontal lobe, specifically in superior longitudinal fasciculus, superior corona radiata, the body of the corpus callosum, inferior frontal and supplementary motor WM, and the aslant tract. The superior longitudinal fasciculus (connecting the frontal lobe to temporal and parietal cortices) has previously been associated to processing speed ( Turken et al, 2008 ) and working memory ( Rizio and Diaz, 2016 ) and impairment of the corona radiata (connecting the prefrontal cortex to the basal ganglia and thalamus) has also been associated to executive dysfunction ( Hua et al, 2014 ; Moeller et al, 2015 ). Interestingly, the aslant tract (connecting the SMA with the inferior frontal cortex) has been associated with the self-initiated movement and speech production ( Kinoshita et al, 2015 ) and its integrity correlated with the amount of distortion errors that PNFA patients made in spontaneous speech ( Mandelli et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…If this were the case, CD would be expected to respond based on information within the first-processed letters while ignoring any information presented in latter letters, resulting in apparently neglect dyslexic reading impairment. It seems possible that CD's reading performance may have been impacted by executive deficits, especially given that CD's lesion impacted basal ganglia white matter tracts which have been found to be significantly associated with executive functioning (Hua et al, 2014;Vataja et al, 2003).…”
Section: Discussionmentioning
confidence: 99%